Pengaruh Pemberian Berbagai Jenis Pakan Terhadap Pertumbuhan Dan Tingkat Kelulushidupan Ikan Silih (Macrognathus aculeatus) [The Effect Of Vary Feed On Growth And Survival Rate Of Spiny Eel (Macrognathus aculeatus)] - Akhmad Taufiq Mukti; Denta Batara Kusuma Hendra; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract The purpose of this research was to know the effect of kinds of feeding on growth and survival rate of spiny eel. This research used experimental method and Completely Random Design method with six treatment and each treatment was replicated four times. The treatments are : artificial feed (A), nila fish (B), shrimp (C), combination of artificial feed with nila fish (D), combination of artificial feed with shrimp (E) and combination of nila fish with shrimp (F). The main parameter observed are specific growth rate, growth of absolute length and survival rate. The support parameter is water quality. The data analiysis of this research used a Analysis of Varian (ANAVA) and to determine the best performed used Duncan's Multiple Range test. The result of this research showed that given kinds of feeding was not significantly difference (p>0,05) to specific growth rate, growth of absolute length and survival rate of spiny eel. The average value of growth of absolute length, specific growth rate and survival rate of each treatment are treatment C (2,5062 mm), treatment C (0,9375 %BT/hari) and treatment C (71,6495%).